Molecular epidemiology of hepatitis B virus from blood samples obtained from persons in Enugu and Nasarawa States, Nigeria - Kingsley Andrew Egbe; Anthony C. Ike; Olusola Anuoluwapo Akanbi; Richard Olulowo Ojedele; Khadijah Isa Imam; Chimaobi Chukwu; Friday Egbe; Edith Silas Ekwom; Nse F. Unam; Ikeata Kenneth Chukwuemeka (BMC Infectious Diseases)
Abstract Hepatitis B virus (HBV) infection remains a major global health concern, with a high burden in countries like Nigeria. This study aimed to investigate the molecular epidemiology of HBV by identifying circulating genotypes and detecting antiviral-resistant mutations in samples from selected communities in Enugu and Nasarawa States, Nigeria. Sample (plasma and serum) quality was evaluated after prolonged storage under freeze-thaw conditions using Qubit 4 fluorometer and Nanodrop One spectrophotometer. High-quality samples underwent molecular characterization and Sanger sequencing for HBV-positive cases. Of the 67 samples analyzed, seven were sequenced: two from Enugu and four from Nasarawa belonged to genotype E, while one from Nasarawa was genotype A. No antiviral resistance mutations were identified. This study provides valuable molecular data contributing to our understanding of HBV epidemiology in Nigeria.